A study on the phylogenetic relationship of the genus cynopterus inferred from mitochondrial dna cytochrome oxidase I (COI) gene - Roberta Chaya Tawie, anak Tingga. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Cynopterus is known to be the most diverse and widely distributed genus among the genera of Old World fruit bats. They are known with the presence of cryptic species within C. brachyotis population. Thus, this study was done to reconstruct the phylogenetic tree of genus Cynopterus (c. brachyotis, C. horsfieldi and C. sphinx) using 482 bp mtDNA cytochrome oxidase I (COl) gene. Twelve samples obtained from Sarawak and Peninsular Malaysia was used in this study. The neighbor-joining and maximum parsimony methods supported previous studies that the genus C. brachyotis is monophyletic and was resolved into four distinct groups.